The Image of the Celestial Empire in American Cartoons During the Yihetuan Movement (1899–1901) - P’yatnychuk, Taras (Narzędzia wojny, 2023)
In the article analyzes the image of Manchurian China in American political cartoons on the eve and during the Yihetuan Movement. In the second half of the 19th century in the USA appeared a number of magazines which specializing in political cartoons. Such magazines as „Harper’s Weekly”, „Puck” and „Judge”, whose cartoons looked like works of art, held leading positions among them. Cartoonists, were raising acute economic, political and social issues in their works, not only actualized them, but also were forming public opinion. Foreign policy problems weren’t left outside also. The object attention of American caricaturists at the end of the 19th – early of the 20th century was China, what were caused by the US economic interests in this region. American caricature portrayed the Chinese and China as a backward barbarian or a treacherous official, which didn`t want to keep pace with progress. The beginning of the Yihetuan Movement and participation of the American troops in its suppression had a significant impact on the image of „Celestial Empire”. A bloodthirsty barbarian and a huge dragon, which was bringing only destruction and anarchy, replaced the backward Chinese barbarian in the cartoons. The dominance of such images fully corresponded to the then ideas about the civilizing mission of the US, and became a part of the myth of the so-called "Yellow Peril".